Regulation of GABAA and 5-HT Receptors Involved in Anxiolytic Mechanisms of Jujube Seed: A System Biology Study Assisted by UPLC-Q-TOF/MS and RT-qPCR Method - Chen, Liang; Zhang, Xue; Hu, Chun; Zhang, Yi; Zhang, Lu; Kan, Juntao; Li, Bo; Du, Jun (Frontiers in Pharmacology, 2020)
The increase of prevalence of anxiety poses great impact on the quality of life in China and globally. As the most popular traditional Chinese medicinal ingredient for nourishing hearth and tranquilizing mind, Jujube seed (Ziziphus jujuba Mill., Rhamnaceae) (SZJ) has been proved to exert anxiolytic effects in previous reports. In this study, a system biology method assisted by UPLC-Q-TOF/MS and RT-qPCR was developed to systematically demonstrate the anxiolytic mechanisms of SZJ. A total of thirty-five phytochemicals were identified from SZJ extract (Ziziphus jujuba Mill. var. spinosa (Bunge) Hu ex H.F. Chow.), which interact with 71 anxiolytic targets. Protein-protein interaction, genes cluster, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis were subsequently conducted, and results demonstrated that regulation of serotonergic and GABAergic synapse pathways was dominantly involved in the anxiolytic mechanisms of SZJ extract. The effects of SZJ extract on mRNA expressions of multiple GABAA (gamma-aminobutyric acid type A) and 5-HT (serotonin) receptors subtypes were further validated in human neuroblastoma SH-SY5Y cells using RT-qPCR. Results showed that SZJ extract (250 μg/mL) significantly up-regulated the mRNA level of GABRA1 and GABRA3, as well as HTR1A, HTR2A and HTR2B in non-H2O2 treated SH-SY5Y cells. However, it exerted an inhibitive effect on the overexpressed mRNA of GABRA1, GABRA2, HTR1A and HTR2A in H2O2 treated SH-SY5Y cells. Taken together, our findings suggest that anxiolytic mechanisms of SZJ mostly involve the regulation of GABAergic and serotonergic synapse pathways, especially a two-way modulation of GABRA1, HTR1A and HTR2A. Our current results provide potential direction for future investigation of SZJ as anxiolytic agent.